2018
DOI: 10.1101/339432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced synaptic properties of the prefrontal cortex and hippocampus after learning a spatial working memory task in adult male mice

Abstract: Development of novel pharmaceutical compounds for neuropsychiatric disorders, and particularly for the cognitive symptoms of these disorders, is a significantly slow and expensive process. Alternate therapeutic regimens include cognitive training, a particular form of which is working memory training (WMT). WMT has been suggested to improve several cognitive functions, although the results in the scientific literature are conflicting.However, we still do not understand the neurobiological basis that could expl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Additional research is needed to better understand potential long-term effects of adolescent consumption of fat and sugar on risk for cognitive decline in late life as well as to identify effective approaches prevention and intervention. One candidate for study may be working memory training as this has been shown to improve reference memory, reversal learning, and synaptic plasticity in rodents (Ioakeimidis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additional research is needed to better understand potential long-term effects of adolescent consumption of fat and sugar on risk for cognitive decline in late life as well as to identify effective approaches prevention and intervention. One candidate for study may be working memory training as this has been shown to improve reference memory, reversal learning, and synaptic plasticity in rodents (Ioakeimidis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%